Adoptive cell therapy for high grade gliomas using simultaneous temozolomide and intracranial mgmt-modified γδ t cells following standard post-resection chemotherapy and radiotherapy: current strategy and future directions - Nabors, L. B.; Lamb, L. S.; Goswami, T.; Rochlin, K.; Youngblood, S. L. (Frontiers in Immunology, 2024)
Cellular therapies, including chimeric antigen receptor T cell therapies (CAR-T), while generally successful in hematologic malignancies, face substantial challenges against solid tumors such as glioblastoma (GBM) due to rapid growth, antigen heterogeneity, and inadequate depth of response to cytoreductive and immune therapies, We have previously shown that GBM constitutively express stress associated NKG2D ligands (NKG2DL) recognized by gamma delta (γδ) T cells, a minor lymphocyte subset that innately recognize target molecules via the γδ T cell receptor (TCR), NKG2D, and multiple other mechanisms. Given that NKG2DL expression is often insufficient on GBM cells to elicit a meaningful response to γδ T cell immunotherapy, we then demonstrated that NKG2DL expression can be transiently up-regulated by alkylating agents such as Temozolomide (TMZ). To avoid the toxic effect of TMZ on γδ T cells, we genetically engineered γδ T cells using a P140K-MGMT vector that confers TMZ resistance to γδ T cells by production of MGMT, a therapeutic system that we termed Drug Resistance Immunotherapy (DRI). This modification enables dosing of TMZ with simultaneous intracranial infusion of MGMT-modified γδ T cells and is now in a first-in-human Phase I clinical trial (NCT04165941). This manuscript will discuss DRI as a rational therapeutic approach to newly diagnosed GBM and the importance of repeated administration of DRI in combination with the standard-of-care Stupp regimen in patients with stable minimal residual disease.